2010
DOI: 10.1007/s11159-010-9152-1
|View full text |Cite
|
Sign up to set email alerts
|

The Right to Education for Children in Domestic Labour: Empirical Evidence from Kenya

Abstract: Since 1948, various UN conventions have recognised basic education as a human right. Yet this right continues to be denied to many child labourers across the world. This articles draws on the results of a study examining how children in domestic labour in Kenya access and participate in education. Three issues were explored: (1) the correlates of child domestic labourers; (2) their working conditions and contexts; and (3) the right to education. Interviews and group discussions held in one city and two rural d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Importantly, attending school makes children visible, providing a form of protection and social capital in the form of friendship, social activities and supportive adults. Education also increases options, gives hope for the future, and offers a potential escape from long term domestic drudgery 15 16. Linked to this is the strong protective factor of social capital per se, which in this context consists of relationships with other CDWs, adult support, and attending a community group, illustrating the importance of support networks for well-being.…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, attending school makes children visible, providing a form of protection and social capital in the form of friendship, social activities and supportive adults. Education also increases options, gives hope for the future, and offers a potential escape from long term domestic drudgery 15 16. Linked to this is the strong protective factor of social capital per se, which in this context consists of relationships with other CDWs, adult support, and attending a community group, illustrating the importance of support networks for well-being.…”
Section: Discussionmentioning
confidence: 97%
“…Child domestic workers' diverse perspectives have now been recorded by scholars and activists across several countries (Camacho 1999;Kifle 2002;Phlainoi 2002;Jacquemin 2004;Rubenson et al 2004;Klocker 2007Klocker , 2011Klocker , 2012aBlagbrough 2008;Bourdillon 2009;Munene and Ruto 2010;Wasiuzzaman and Wells 2010). Unlike the children they employ, employers' motives and experiences have rarely been documented and their reputations have taken a battering -particularly in studies likening child domestic work to slavery (Janak 2000;Blagbrough 2008;Derby 2009).…”
Section: Looking Beyond Children: Majority World Employers and Child mentioning
confidence: 99%
“…A few studies have asked employers to reflect on children's experiences of domestic employment (Jacquemin 2004;Munene and Ruto 2010;Wasiuzzaman and Wells 2010), but I have found only one that explicitly asked employers what child domestic work meant to them and how it affected their lives (Phlainoi 2002). This article neither seeks to deny the existence of exploitative and abusive employers, nor to provide a sanitised version of their conduct.…”
Section: Looking Beyond Children: Majority World Employers and Child mentioning
confidence: 99%
“…Various studies have identified reasons for exclusion of these children from formal schools. These include: a) child labor, b) children infected and/or affected by HIV/AIDS, c) children from pastoralist communities (Sifuna, 2005), d) children with disabilities (Ananga, 2011;Birger & Crassati, 2009;Burnet, 2008;Githitho-Muriithi, 2010;Ministry of Education Science and Technology, 2005;Munene & Ruto, 2010;Mutua & Dimitrov, 2001;Nyambedha, Wandibba, & Aagaard-Hansen, 2000;Sifuna, 2005; UNESCO, 2010), e) the girl child (Glick, 2008;Kane, 2004;Lloyd, Mensch, & Clark, 2000 This statement suggests that children orphaned due to HIV and AIDS are at risk of dropping out of schools if enrolled or risk being excluded altogether. The risk is higher when the mother is involved since she is assumed to be the primary caretaker of the family when she dies, older children are forced to assume the caretaker role and thus drop out of school (Birger & Crassati, 2009;Swadener, Kabiru, & Njenga, 2000).…”
Section: Children Still Excluded From Full Benefits Of Fpementioning
confidence: 99%
“…The Kenya population census conducted in 2009 confirmed findings from various studies which indicated that not all children are accessing primary education in Kenya. These studies have identified categories of children who are left out in accessing primary education and include: (a) orphans (UNESCO, 2010;Birger & Craissati, 2009); (b) children engaged in labor, (Githitho-Muriithi, 2010;Munene & Ruto, 2010); (c) children from pastoralists (nomadic) communities (Sifuna, 2005); (d) children with disabilities (Birger & Craissati, 2009;Oriedo, 2003;Mukuria & Korir, 2006;Bore, Mukuria, & Adera, 2007) and e) the girl child (Glick, 2008;Kane, 2004;Lloyd, Mensch, & Clark, 2000;Southern and Eastern Africa Consortium for Monitoring Educational Quality-SACMEQ, 2011; Shabaya & Konadu-Agyemang, 2004). While some of these children may initially enroll in primary schools, a study by Ackers, Migoli, & Nzomo (2001) reports that many children drop out of schools between grades 1 and 2, and grades 6 and 7 due to "paucity of the school environment and poor performance" (p. 365) whereby teachers and students in these schools do not have access to adequate and appropriate instructional materials, thereby priming these students for failure.…”
Section: Introductionmentioning
confidence: 99%